1995
DOI: 10.1016/0014-5793(95)01191-g
|View full text |Cite
|
Sign up to set email alerts
|

The recombinant GABA transporter GAT1 is downregulated upon activation of protein kinase C

Abstract: Treatment of human embryonic kidney 293 cells expressing the rat ~/-aminobutyric acid (GABA) transporter 1 (GATI) with the protein kinase C (PKC) activator phorbol 12-myristate 13-acetate (PMA) was found to decrease the velocity of specific [3H]GABA uptake. This downregulation varied with extracellular GABA concentration and was blocked by the PKC inbibitors 1-(5-isoquinolinylsulphonyl)-2-methylpiperazine 017) and staurosporine. An about 50% reduction of uptake velocity by PMA treatment was observed at GABA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…In addition to the translocation of GAT1 by PMA observed in our studies, independent investigations have shown that, under certain conditions and in different cell types, phorbol esters can exert other effects on GABA transporter function, including: (1) increasing the K m for GABA in oocytes twofold (Osawa et al, 1994); and (2) decreasing V max 50% (at GABA concentrations Ďž1 M) in 293 cells (Sato et al, 1995). To further understand the mechanisms underlying these multiple effects of phorbol ester treatment and to minimize their impact on the present studies, we examined changes in [ 3 H]GABA uptake and resting membrane potential after different PMA applications.…”
Section: Coinjection Of Rat Brain Mrna Permits Pma-induced Modulationsupporting
confidence: 62%
“…In addition to the translocation of GAT1 by PMA observed in our studies, independent investigations have shown that, under certain conditions and in different cell types, phorbol esters can exert other effects on GABA transporter function, including: (1) increasing the K m for GABA in oocytes twofold (Osawa et al, 1994); and (2) decreasing V max 50% (at GABA concentrations Ďž1 M) in 293 cells (Sato et al, 1995). To further understand the mechanisms underlying these multiple effects of phorbol ester treatment and to minimize their impact on the present studies, we examined changes in [ 3 H]GABA uptake and resting membrane potential after different PMA applications.…”
Section: Coinjection Of Rat Brain Mrna Permits Pma-induced Modulationsupporting
confidence: 62%
“…Protein kinase C activation have also been recently shown to modulate the activity of other cloned cotransporters expressed in oocytes and HEK 293 cells [22][23][24][25][26]. The Na/Pi (NaPi-2), Na/Cl/glycine (GLYTlb) cotransporters were inhibited [23,24] and the Na/CI/GABA (GAT1) cotransporter was stimulated after activation of PKC [22].…”
Section: Discussionmentioning
confidence: 99%
“…3 [22,26]); arachidonic acid reduces the maximal rate of transport by the human Na/glutamate transporter (EAAT1) but stimulates transport by the human EAAT2 isoform [29]. The action of the kinases also depends on the cell type: PKC stimulates the rat GABA transporter expressed in oocytes but inhibits it HEK 293 cells [22,25]. The physiological significance of the differential modulation of cotransporter isoforms by kinases, and the dependence of the kinase action on the cell type are puzzling.…”
Section: Discussionmentioning
confidence: 99%
“…GAT1 is also down-regulated after activation of PKC (Osawa et al, 1994;Sato et al, 1995b;Beckman et al, 1998Beckman et al, , 1999Bahena-Trujillo and Arias-MontaĂą o, 1999;Quick et al, 2004;Wang and Quick, 2005;CristĂłvĂŁo-Ferreira et al, 2009), but only one study has demonstrated increased transporter phosphorylation upon PKC stimulation (Quick et al, 2004). PKC-mediated Geerlings et al, 2000Geerlings et al, , 2001 N.I., not identified; CIPP, channel-interacting PDZ protein; SNAP-25, synaptosome-associated protein 25; NEDD4-2 (neural precursor cell expressed, developmentally down-regulated 4-2); GPR37, G protein-coupled receptor 37; ARFGAP1, ADP-ribosylation factor GTPase-activating protein 1; Pals1, protein associated with Lin seven 1; Ulip6, Unc-33-like protein 6.…”
Section: Phosphorylation a Protein Kinase C-mediated Phosphorylationmentioning
confidence: 99%